Prophylaxis of venous and pulmonary thrombo-embolism. - Yusimí Isaguirre Martínez; José Julio Requeiro Molina; Hugo Jiménez Vázquez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
This bibliographical revision stands out the importance of the vein thromboembolism prevention in patients under different surgical and injuries procedures, wicked illnesses and medical conditions. The epidemiology, etiopatogenia and factors of risk of the deep vein thrombosis and the lung embolism are exposed in different categories of patient. Up to dates prophylactic methods are taken into account and compared their effectiveness and cautions according to the last studies on the topic.